Extraction of the species-dependent dipole amplitude and phase from high-order harmonic spectra in rare-gas atoms - Le, Anh-Thu; Morishita, Toru; Lin, C. D. (My University, 2008)
Based on high-order harmonic generation (HHG) spectra obtained from solving the time-dependent Schrödinger equation for atoms, we established quantitatively that the HHG yield can be expressed as the product of a returning electron wave packet and photorecombination cross sections, and the shape of the returning wave packet is shown to be largely independent of the species. By comparing the HHG spectra generated from different targets under identical laser pulses, accurate structural information, including the phase of the recombination amplitude, can be retrieved. This result opens up the possibility of studying the target structure of complex systems, including their time evolution, from the HHG spectra generated by short laser pulses.